An exact approach for radius of curvature measurement in a calibration test sphere - Jalife-Chavira, Jaime M.; Trujillo-Schiaffino, Gerardo; Mendoza-Villegas, Paloma G.; Salas-Peimbert, Didia Patricia; Anguiano-Morales, Marcelino; Corral-Martínez, Luis F.; Zendejas-Hernández, Edgar (Oficyna Wydawnicza Politechniki Wrocławskiej, 2022)
In this paper we present a technique to measure the radius of curvature of a test sphere based on the relation between acquired images of a circular cosine fringe pattern and size of virtual image formed on the calibration test surface. Radius of curvature is calculated with the exact equation proposed, using the parameters of the optical setup. Fringe pattern evaluation was performed by locating extrema indices. The mathematical formulation as well as the experimental setup and results are presented. After applying a linear fit algorithm to the data as a method of compensation, obtained results show an error within the tolerance established by the ISO 10343 specifications.
Optica Applicata, Vol. 52, 2022, nr 2, s. 229-242
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; keratometry; radius of curvature; diopters; cosine fringe pattern; film